Conexões entre padrões de precipitação no nordeste da América do Sul e a produtividade primária no oeste do Oceano Atlântico Sul durante o último deglacial - Martins, Alisson Klayton (Universidade do Vale do Rio dos Sinos, 2021)
It is a known-well fact that global temperatures and sea levels are rising, rainfall patterns are changing, and extreme weather events are becoming more intense and destructive. In this sense, geology plays a crucial role to understand how climate has changed in the past and assist in predictions of current and future climate shifts. In this work we discuss how a change in the Atlantic Meridional Overturning Circulation (AMOC) can cause climatic anomalies over northeastern South America. The possibility of a collapse (or sharp weakening) of the AMOC within a few centuries has increased the scientific community's interest in responses from different compartments of the Earth system to previous collapses of AMOC (or sharp weakening). The most recent examples of these periods are Heinrich Stadial 1 (HS1,18-15 ka BP; AMOC almost collapsed) and the Younger Dryas (YD, 12.9-11.7 ka BP; AMOC markedly weakened). Here, we present elemental ratios, organic biomarkers, reconstructions of sea surface temperature and data from planktonic foraminiferal assemblages of a marine sediment core recovered from the western tropical South Atlantic Ocean that extends through the last ca. 20 kyr. The core records hydroclimate responses of tropical South America and productivity changes in the western tropical South Atlantic during AMOC intensity fluctuations associated with HS1 and the YD. Our data show that both HS1 and the YD were characterized by wetter climates over the northeastern South America and, consequently, there was an increase in continental runoff. However, continental runoff was probably more intense during HS1, when nutrient supply increased primary productivity in the western tropical South Atlantic Ocean. Together with previously published data, we suggest that marked decreases in AMOC intensity during HS1 and the YD trapped heat in the surface layer of the western South Atlantic Ocean, facilitating humidity transfer and increasing precipitation over northeastern South America.
Keywords: Mudanças climáticas; Paleoclimatologia; Precipitação; América do Sul; Heinrich Stadial; Younger Dryas; Climate change; Paleoclimatology; Precipitation; South America; ACCNPQ::Ciências Exatas e da Terra::Geologia